Synthesis of 3-(1, 3-Diphenyl-1H-pyrazol-4-yl) Propanoic Acids Using Diimide Reduction - M. Deepa; V. Harinadha Babu; R. Parameshwar; B. Madhava Reddy (E-Journal of Chemistry)
Pyrazole-1H-4-yl-acrylic acids (3a-j) were prepared from pyrazole-1H-4-carbaldehydes which in turn were prepared by the Vilsmeier-Haack reaction of phenyl hydrazone derivatives (1a-j). The reaction of pyrazole-1H-4-yl-acrylic acids to 3-(1, 3-diphenyl-1H-pyrazol-4-yl) propanoic acids (4a-j) was carried out using Pd-charcoal and diimide methods and % yields were compared. Though the yields may be slightly less in diimide method, the method was found to be economical, highly effective with simple operating procedure.